Productivity of some browse plants on acid soils of southeastern Nigeria - Cobbina, J.; Atta-Krah, A.N.; Meregini, A.D.; Duguma, B. (1990)
Presents results of experiments to assess yields of Leucaena leucocephala and Gliricidia sepium and to compare these with those of the indigenous browse plants Acioa bacteria, Alchornea cordifloca and Albizia adianthifola on acid soils in Nigeria.